Predation on cattle in Kenya and its effect on the stress level of the animals in the exposed herd - Eriksson, Linda (SLU/Dept. of Animal Environment and Health (until 231231), 2017)
Predation on livestock affects the human-carnivore conflict and can also lead to great economical loss for farmers. Lions are the predator that attacks the most cattle in Kenya, but there are also attacks from hyenas, leopards and jackals. Predation on livestock is a worldwide problem and it is therefore of big importance to investigate how the predator attacks are affecting the cattle that survived in the exposed herd. If predator attacks leads to chronic stress in the cattle, it can affect the reproduction cycle of the animals, the health and also their productivity. In this study two herds that had been attacked by predators during the last 10 months (one herd with cows and one herd with steers), and also two control herd that had not suffer from any attacks during the same time were chosen to be analyzed for hair cortisol as an indicator of stress. Hair samples were collected from the tail switch from 10 random individuals from each of the four herds and then analyzed for cortisol, as cortisol gets deposit in the hair constantly as it grows. The result in cortisol indicates that there was no significant difference between attacked and non-attacked herds or between steers and cows. There is also no significant difference in cortisol levels between animals with different body condition scores. There was a significant difference in cortisol levels in the color of the hair, with light hair containing the highest amount of cortisol.